(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Currently, kyrgyz terminology is experiencing a phase of active development under the influence of complex, contradictory changes in normative-institutional and practical-discursive factors. In the context of ongoing modernization, digitalization, and globalization in society, the terminological system of the kyrgyz language is developing in two interconnected, but often contradictory, planes: codification and communicative-practical. The boundaries between normative and codification approaches reflect the institutional level of creation and regulation of terminology. The implementation is carried out through the activities of state and scientific structures, primarily the Terminology commission of the National commission on the state language and language policy under the President of the Kyrgyz Republic, as well as specialized research institutes and publishing houses of terminological dictionaries. The article analyzes the stability, transparency, and standardization of terminology. It also describes the history, development, and activities of the Kyrgyz terminology commission. Particular attention is paid to a comprehensive examination of current issues